Komodifikasi Tubuh Perempuan Dalam Pornografi Digital (Analisis Wacana Kritis Film Dokumenter ‘Hot Girls Wanted’) - Sofia Hasna (Universitas Muhammadiyah Surakarta, 2023)
Pornography has always been a problem discourse because it can violate standard social rules, especially containing elements of commodification and exploitation of women's bodies. Commodities and exploitation of women's bodies also occur in the liberalization of pornography in today's digital era, which is depicted in the 2015 documentary film 'Hot Girls Wanted' by Jill Bauer and Ronna Gradus which tells about teenage girls who have chosen to work in pornography. imprecisely to statistics about online pornographic viewing shown during the film. So that the formulation of the problem in this research is how the conversation and text of the documentary film 'Hot Girls Wanted' represents the commodity of the female body in the liberalization of digital pornography which is analyzed using the critical discourse analysis of Sarah Mills's approach. The purpose of this study is to disassemble the discourse in the documentary to see the commodification of the female body in the liberation of digital pornography. The analytical method used is qualitative research, critical discourse analysis, Sarah Mills's approach using a feminist perspective. The results of this study indicate the practice of commodification of women's bodies in the documentary film 'Hot Girls Wanted', where the pornography industry perpetuates the practice of patriarchal domination and women only as objects to satisfy lust or the male gaze so that women are placed as marginalized objects and the presence of hegemony in the porn industry, women perpetuate gender bias.Keywords: Porn Industry; Commodification; Women’s Bodies; Movie